Radiative Effect of Clouds at Ny-Alesund, Svalbard, as Inferred from Ground-Based Remote Sensing Observations - Ebell, Kerstin; Nomokonova, Tatiana; Maturilli, Marion; Ritter, Christoph (AMER METEOROLOGICAL SOC, 2020)
For the first time, the cloud radiative effect (CRE) has been characterized for the Arctic site Ny-Alesund, Svalbard, Norway, including more than 2 years of data (June 2016-September 2018). The cloud radiative effect, that is, the difference between the all-sky and equivalent clear-sky net radiative fluxes, has been derived based on a combination of ground-based remote sensing observations of cloud properties and the application of broadband radiative transfer simulations. The simulated fluxes have been evaluated in terms of a radiative closure study. Good agreement with observed surface net shortwave (SW) and longwave (LW) fluxes has been found, with small biases for clear-sky (SW: 3.8 W m(-2); LW: -4.9 W m(-2)) and all-sky (SW: -5.4 W m(-2); LW: -0.2 W m(-2)) situations. For monthly averages, uncertainties in the CRE are estimated to be small (similar to 2 W m(-2)). At Ny-Alesund, the monthly net surface CRE is positive from September to April/May and negative in summer. The annual surface warming effect by clouds is 11.1 W m(-2). The longwave surface CRE of liquid-containing cloud is mainly driven by liquid water path (LWP) with an asymptote value of 75 W m(-2) for large LWP values. The shortwave surface CRE can largely be explained by LWP, solar zenith angle, and surface albedo. Liquid-containing clouds (LWP > 5 g m(-2)) clearly contribute most to the shortwave surface CRE (70%-98%) and, from late spring to autumn, also to the longwave surface CRE (up to 95%). Only in winter are ice clouds (IWP > 0 g m(-2); LWP < 5 g m(-2)) equally important or even dominating the signal in the longwave surface CRE.